A randomized, double-blind, placebo-controlled trial investigating cholesterol-lowering effects and safety of yellow yeast rice in adults with mild to moderate hypercholesterolemia: A study protocol. Issue 30 (July 2018) - Jeong, Sewon; Lee, Jaekyung; Kwon, Oran; Kim, Ji Won; Oh, Bumjo
Abstract: Background: Elevated levels of blood lipids are well-documented risk factors for cardiovascular disease. For cardiovascular risk reduction, preventive strategies to lower blood cholesterol levels are essential, and these strategies include lifestyle modification and cholesterol-lowering agents. We aim to investigate the cholesterol-lowering effects and safety of yellow yeast rice in a randomized, controlled, double-blind, and parallel group study. Methods: Participants for this study will be selected based on the following inclusion criteria: Voluntary agreement to participate and sign the written informed consent forms Men and women (aged 20–45 years, premenopause) Body mass index: 18 to 30 kg/m2 Fasting low-density lipoprotein cholesterol (LDL-C) levels: ≥130 mg/dL Fasting triglyceride levels: <300 mg/dL Participants are randomly allocated to the placebo or yellow-yeast-rice-treated group. Participants with mild to moderately elevated LDL-C levels will consume 1 pouch of yellow yeast rice powder (containing monacolin K) or placebo twice daily for 8 weeks. Next, the lipid profiles will be evaluated. Results: The number of participants required for this study is 68, and is currently recruiting participants. Participants are randomly assigned to control group and intervention group. Conclusion: This is the first human intervention study to investigate the cholesterol-lowering effects and safety of yellow yeast rice in adults with mild to moderate hypercholesterolemia. Also, this is a randomized, double-blind, placebo-controlled trial that considers confounders, such as dietary habits, lifestyle factors, and genetic factors.